Smile toothgether : an early childhood oral health campaign - Lim, Keith Wen Xuan (Nanyang Technological University, 2021)
This paper presents a health communication campaign “Smile Toothgether”, by Queenie, Keith, Gladys, and Rebecca, four final year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University, Singapore. The campaign was designed and launched in response to tackle the high incidence of early childhood caries (ECC) among children below the age of six in Singapore. This paper details Smile Toothgether’s research, campaign development, and evaluation. Secondary research revealed that the prevalence of early childhood oral health-related issues such as dental caries were increasingly evident globally as well as in Singapore. This was due to transmission of bacteria species, poor feeding practices, and inadequate oral health practices. Dentists recommend that parents first bring their children to the dentist by the age of one, but most parents did not do so, only making an appointment when oral health problems arose. Primary research revealed that parents held many misconceptions surrounding cariogenic substances, dental visits, and administering oral care routines for their children below the age of six. This was accompanied by high perceived self-efficacy, meaning that many parents in Singapore were overconfident when it came to caring for their children’s oral health. Smile Toothgether was launched and targeted at parents with children aged six years and under. The campaign tactics utilised tailored content and several online interactive approaches to educate parents on the benefits of early preventive oral health behaviours. The campaign also communicated the importance of early dental visits to minimise the onset of ECC. The campaign was effective, amplifying risk perception of cariogenic substances and early oral health diseases in the target audience. The campaign also decreased the perceived financial costs of early dental visits, increasing their perceived accessibility to parents. Despite the campaign’s success, its post-campaign research indicated that further sustained communication efforts are necessary to fight ECC in Singapore.